Description of the Event of Irritant Contact Dermatitis in Employees of the Home Industry Batik - Dewi Saroh; Purwati Purwati; Tri Harningsih (GLOBAL HEALTH SCIENCE GROUP, 2022)
Batik is one of Indonesian culture which has high artistic value. The dyes used in the batik industry can come from natural dyes and synthetic dyes. Synthetic dyes contain hazardous chemical compounds in the form of heavy metals. Heavy metal compounds can cause cancer in living things. Contact with chemicals, such as workers in the batik industry can cause various skin disorders. One of the skin disorders that occurs due to exposure to chemicals is contact dermatitis. Based on research data from 21 employees of the coloring division in the batik home industry, the prevalence of irritant contact dermatitis was 33.33% (7 people) with the most characteristic age being 40-70 years, working duration >5 years, exposure contact duration 0-3 hours. / day, the most common symptoms are itching that occurs on the palms of the hands, backs of hands, forearms, between the fingers, and the backs of the feet. Respondents who had a history of atopic dermatitis were only 9.52% (2 people), and for exposure to chemicals other than batik dyes only 19.05% (4 people). Other chemicals that trigger contact dermatitis are detergents and fragrances. From the incidence of irritant contact dermatitis to employees of the coloring department in the batik home industry, more employees choose to be left alone than treated because the symptoms that appear are mild and do not interfere with work activities.